It's snow problem - Butcher, Nancy (HarperEntertainment New York, 2001)
Hans Jensen is tall, blond, goreous, and thinks he's the best at everything. When he signs up for every ski race in the White Oak/Harrington Winter Festival, Mary-Kate does too. Then Mary-Kate gets into major toruble and is thrown off all the teams. Can Ashley help her sister?